Reducing forest and land fires through good palm oil value chain governance - Purnomo, H.; Okarda, B.; Dewayani, A.A.; Ali, M.; Achdiawan, R.; Kartodihardjo, H.; Pacheco, P.; Juniwaty, K.S. (Elsevier, 2018)
United Nations' Sustainable Development Goals (SDGs) aim to protect the planet and ensure prosperity. In reaching SDGs, Indonesia's palm oil industry represents a solution for the economy but a problem for environment-related goals. Palm oil is a tremendous land-based commodity that supports the subnational and national economies of Indonesia. With 11.4 million ha of plantations, palm oil has contributed USD 20.75 billion in 2015 to Indonesia's export income. However, fire has been involved in the development and replanting of palm oil plantations. Smoke haze from fires harm the economy, the environment, and the health of millions of people. The research took a normative approach to understand whether the current palm oil value chain governance comply with the principle of good governance. The focus was on analyzing options to improve the current governance towards good governance, which is able to reduce fire uses. We reviewed previous investigations, and carried out focus group discussions, field interviews, and value chain analysis. We found that the palm oil economy distributed enormous value added to those participating in the chain. However, the fire uses in land preparation can be altered by using coercion, dis(incentives) and dominant information that held by district and central governments, growers and mil. The potential benefits from green products, a strengthened growers' association, moving up scenarios can be used to compensate the 'benefits' of using fire. Lessons learnt from the palm oil commodity chain in Indonesia, when the economy and the environment are contested, can be used by other countries to reach towards their SDGs.